A CCL25 chemokine functions as a chemoattractant and an immunomodulator in black rockfish, Sebastes schlegelii. Issue 100 (May 2020) - Wang, Jingjing; Meng, Zhaoqi; Wang, Guanghua; Fu, Qiang; Zhang, Min
Abstract: Chemokines are small cytokines that are classified into four groups, one of which is called CC chemokines. In the present study, the full-length cDNA of a CCL25 chemokine was identified from black rockfish, Sebastes schlegelii (named as SsCCL25) by EST (expressed sequence tag) analysis. The cDNA of SsCCL25 consisted of a 5-terminal untranslated region (UTR) of 74 bp, a 3-UTR of 882 bp with a poly (A) tail, and an open reading frame (ORF) of 303 bp encoding a polypeptide of 100 amino acids with the putative molecular mass of 11.5 kDa. There was a SCY domain in the deduced amino acid sequence of SsCCL25. The phylogenetic relationships and syntenic analyses provided evidences for the identities of SsCCL25 with CCL25 group. The mRNA transcripts of SsCCL25 were expressed in all detected tissues and dominantly in liver, muscle and gill. Moreover, after Vibrio anguillarum stimulation, the mRNA expression levels of SsCCL25 were significantly up-regulated at 24 h ( p < 0.05) in the liver and during 4–8 h ( p < 0.05) in the spleen. Recombinant SsCCL25 protein induced chemotaxis of both control and LPS-stimulated peripheral blood leukocytes (PBL) and enhanced their resistance to bacterial infection in a dose-dependent manner. Furthermore, rSsCCL25 showed significant inhibitory effect on V. anguillarum and Edwardsiella tarda growth. All these results collectively indicated that SsCCL25 might contribute to the defense against microbe infection and function as a chemoattractant in black rockfish. Highlights: mRNA expression of SsCCL25 in the liver and spleen was upregulated after Vibrio anguillarum infection. rSsCCL25 induced chemotaxis of peripheral blood leukocytes (PBL) and enhanced the resistance of PBL to bacterial infection. rSsCCL25 inhibited growth of Vibrio anguillarum and Ewardsiela tarda.